Analysis on Design Scheme of Autonomous Ship Cooperative Control. Issue 7 (April 2020) - Jing, Mei; Zheng, Weigang
Abstract: During this stage, the technology of autonomous ships is becoming more and more mature, which has been widely used in military or civil fields, especially in the field of marine survey. With the gradual maturity of independent ship technology, the advantages of independent ship such as voyage, manufacturing cost and independent control are increasingly prominent.In spite of the rapid development of related technologies of autonomous ships, autonomous ships alone are still unable to compare with autonomous ship formation. Autonomous formation cooperative work can not only effectively improve the phase ratio of operations, but also greatly improve the fault tolerance and maritime adaptability of operations. Therefore, there is only one main ship out to sea in production practice, most of which are several independent ships to achieve specific goals in cooperation [1]. In order to effectively improve the cooperative control of autonomous ship formation under the interference of harsh environment, such as air volume at sea, a design scheme of cooperative control for autonomous ship formation is proposed in this study. The results show that the design scheme can effectively improve the cooperative control ability of formation.